Eradication therapy for Helicobacter pylori infection based on the antimicrobial susceptibility test in children: A single‐center study over 12 years. Issue 1 (18th October 2020) - Miyata, Eri; Kudo, Takahiro; Ikuse, Tamaki; Tokita, Kazuhide; Arai, Nobuyasu; Oka, Itsuhiro; Kyodo, Reiko; Sato, Masamichi; Hosoi, Kenji; Jimbo, Keisuke; Aoyagi, Yo; Ohtsuka, Yoshikazu; et al.
Abstract: Background: Helicobacter pylori ( H. pylori ) infection causes chronic gastritis, duodenal and to a lesser extent, gastric ulcers, and gastric cancer. Most H. pylori infections are acquired in childhood, and effective treatment of childhood infection is very important. Esophagogastroduodenoscopy (EGD) is useful for endoscopic diagnosis, mucosal tissue biopsy, and culture examination for H. pylori in children and adults. In this paper, we report results of susceptibility tests and eradication rates in H. pylori ‐positive children who underwent EGD over a 12‐year period. Materials and Methods: The subjects were H. pylori ‐positive pediatric patients who had gastrointestinal symptoms and underwent EGD in the Department of Pediatrics, Juntendo University Hospital (January 2007–December 2018). Patients underwent serum IgG antibody tests, fecal antigen tests, or urea breath tests, and subsequently, culture tests by gastric mucosal biopsy during EGD. H. pylori positivity was defined as a positive result on both tests. Patients received triple therapy for 14 days using our regimen, and eradication was assessed at 2, 6, and 12 months after therapy. Results: Forty‐five patients were H. pylori‐ positive, and the overall clarithromycin (CAM) resistance rate was 71.1 % (32/45). The CAM resistance rate for the 2013–2018 period was significantly higher than the 2007–2012 period (52.6% vs. 84.6%, P < 0.05). According to the results of the antimicrobial susceptibility test, we prescribed effective antibiotics, and this resulted in a primary eradication rate of 97.7%. Conclusions: We suggest that antimicrobial susceptibility testing can significantly improve rates of primary eradication of H. pylori infection.